Technique of transurethral needle core biopsy to confirm invasive bladder cancer staging - Chłosta, Piotr (Termedia Publishing House, 2010)
INTRODUCTION: Transurethral, cystoscopically-guided needle core biopsy (TUcoreBxBT) seems to be a less invasive diagnostic method than transurethral resection (TURBT) offering a simple way to confirm cancer infiltration of the bladder. The aim of this study was to assess the technique of TUcoreBxBT in the diagnosis of bladder cancer infiltrating the detrusor muscle. MATERIAL AND METHODS: In every 96 pts the suspicion of invasive bladder cancer (IBC) was evaluated on the basis of radiological examinations, cystoscopy and bimanual examination. TUcoreBxBT were performed using a rigid cystoscope with a direct working channel and tru-cut automatic (COOK Quick-Core(®) Biopsy-Needle) 18 G/480 mm needle or self construction tru-cut 16 G/400 mm needle, adapted to work with a standard biopsy gun. At least three cores were taken in each patient, followed by regular TURBT. RESULTS: There were no complications of the bladder biopsy procedure. The average size of cores was 15 mm (8-17 mm). In every case TUcoreBxBT revealed muscle infiltration and was in agreement with all microscopic examinations of TURBT. CONCLUSIONS: TUcoreBxBT in cases of clear suspicion of invasive bladder cancer is a simple, short and safe procedure which makes it possible to collect reliable material for microscopic examination. TUcoreBxBT is less invasive than standard TURBT only in diagnosis and staging of invasive tumours, and seems to be effective in selected cases to confirm malignancy before radical cystectomy.